The property of having a k ‐regular subgraph has a sharp threshold. Issue 4 (28th May 2012) - Letzter, Shoham
Abstract In this paper it is proved that in the random graph model G(n, p), the property of containing a k ‐regular subgraph, has a sharp threshold for k ≥ 3. It is also shown how to use similar methods to prove, quite easily, the (known fact of) sharpness of having a non empty k ‐core for k ≥ 3. © 2012 Wiley Periodicals, Inc. Random Struct. Alg., 42, 509–519, 2013